HUBUNGAN VERBAL ABUSE DENGAN TINGKAT KECERDASAN EMOSIONAL ANAK KELAS 5 & 6 DI SDN 012 BALIKPAPAN KOTA - Vivin Sumarni Bahdar; Siti Mukaromah; abdurrahman abdurrahman (Jurnal Keperawatan Wiyata, 2021)
VERBAL ABUSE RELATIONSHIP WITH THE LEVEL OF EMOTIONAL INTELLIGENCE OF GRADE 5 & 6 CHILDREN Vivin Sumarni B1, Siti Mukarommah2, Abdurrahman3 Email : vivinsumarni@gmail.com Background The school age as an intellectual period or school harmony. At this age, children acquire basic knowledge and skills for the successful adjustment of children to adult life. The purpose of this study was to analyze whether there is a relationship between verbal abuse and the level of emotional intelligence in grade 5 & 6 children at SDN 012 Balikpapan Kota. This research method is a quantitative study with a correlation analytic design, using a cross-sectional approach. This research technique uses Consecutive Sampling, and uses a questionnaire in the form of google form media with a number of respondents 94 children. The results of this study using the Product Moment Correlation test showed a relationship between verbal abuse and the level of emotional intelligence of children with a value of p = 0.002 <α 0.05. The conclusion is expected for the next researcher to look for the many factors other than verbal abuse that can cause a child's emotional intelligence to be disturbed. Keywords: Verbal Abuse, Emotional Intelligence Level, Elementary School Children